Elevated AA/EPA Ratio Represents an Inflammatory Biomarker in Tumor Tissue of Metastatic Colorectal Cancer Patients - Tutino, Valeria; De Nunzio, Valentina; Caruso, Maria Gabriella; Veronese, Nicola; Lorusso, Dionigi; Di Masi, Marta; Benedetto, Maria Lucrezia; Notarnicola, Maria (International journal of molecular sciences, 2019)
Chronic inflammation increases the risk of developing certain types of cancer, such as colorectal cancer (CRC). The oxidative metabolism of polyunsaturated fatty acids (PUFAs) has a strong effect on colonic tumorigenesis and the levels of arachidonic acid (AA) and eicosapentaenoic acid (EPA) can contribute to the development of an inflammatory microenvironment. Aim of this study was to evaluate the possible differences in the AA/EPA ratio tissue levels between CRC patients with and without synchronous metastases. Moreover, the expression of the most important inflammatory enzymes and mediators, linked with the AA/EPA ratio, have been also assessed. Sixty-eight patients with CRC were enrolled in the study, of which 33 patients with synchronous metastasis. Fatty acid profile analysis in tissue samples was done to examine the levels of AA and EPA. High levels of the AA/EPA ratio were detected in tumor tissue of patients with metastatic CRC. Moreover, an increase of expression of the main enzymes and mediators involved in inflammation was also detected in the same samples. The lipidomic approach of inflammation allows to evaluate lipid homeostasis changes that occur in cancer and in its metastatic process, in order to identify new biomarkers to be introduced into clinical practice.